2019
DOI: 10.4103/japtr.japtr_27_19
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-labeled genistein as a potential radical scavenging agent

Abstract: The purpose of this study was to determine the optimum conditions for labeling genistein compounds with technetium-99m ( 99m Tc) radionuclides and the percentage of purity obtained in accordance with the requirements of the United State Pharmacopeia. The method used is optimization of several parameters including pH, SnCl 2 .2H 2 O as reducing agents, genistein concentration, and incubation time. The results showed that the optimum conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…These results are also in line with the results of optimizing the labeling of genistein compounds with technetium-99m radioisotope with pH 8 as the optimum pH with purity reaching 91.97% ± 1.43% [ 18 ]. Optimization results at pH 8 indicate that this pH approaches physiological conditions, where the mechanism of action of genistein as an estrogen receptor antagonist will be stable, and can perform its function as an estrogen receptor antagonist beta sub unit [ 19 ].…”
Section: Discussionsupporting
confidence: 82%
“…These results are also in line with the results of optimizing the labeling of genistein compounds with technetium-99m radioisotope with pH 8 as the optimum pH with purity reaching 91.97% ± 1.43% [ 18 ]. Optimization results at pH 8 indicate that this pH approaches physiological conditions, where the mechanism of action of genistein as an estrogen receptor antagonist will be stable, and can perform its function as an estrogen receptor antagonist beta sub unit [ 19 ].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, sodium pertechnetate solution [ 99m Tc] with an activity 7.4 -17 MBq was added in the process of forming 99m Tc genistein. The radiochemical purity (RCP) of the complex formation is monitored by TLC and must ful ll the USP requirement of > 90% [14][15] .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies concerning the usage of reducing agents such as stannous derivatives were identified in the literature. , …”
Section: Methodsmentioning
confidence: 99%
“…Incubation time was also determined as a critical parameter in the preparation process of radiopharmaceuticals. Studies have demonstrated that adequate labeling needs a certain amount of time. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation